Lower Trapezius Flap for Reconstruction of Posterior Scalp and Neck Defects after Complex Occipital-Cervical Surgeries - Zenga, Joseph (J Neurol Surg B Skull Base, 2015)
Objectives To review the indications, techniques, and outcomes for a series of patients in whom the lower trapezius flaps was used for repair of complex posterior scalp and neck defects after posterior occipital-cervical surgeries. Design Retrospective case series. Setting Tertiary academic hospital. Participants A retrospective review of cases that required complex occipital-cervical repair was performed to identify patients who underwent reconstruction using the lower trapezius flap. Data collected included demographics, clinical presentations, surgical anatomy, operative techniques, and outcomes with review of the pertinent literature. Outcomes Nine patients who underwent reconstruction using the lower trapezius flap were identified. Prior surgical interventions included five complex tumor resections, two patients with multiple instrumented cervical spine surgeries, one patient with a craniotomy for attempted extracranial to intracranial arterial bypass for a basilar aneurysm repair, and a posterior occipital-cervical decompression after trauma. During the median follow-up period of 7 months, all nine single-stage reconstructions resulted in successful healing without major surgical complications. Conclusion Lower trapezius island flaps provide a reliable option for the reconstruction of complex scalp and neck defects that develop after complex occipital-cervical surgeries.